Sporadic Neurofibroma of the Peritoneal Cavity. Issue 11 (22nd November 2022) - Shah, Rahil H.; Forde, Justin; Arora, Kshitij Satnamdas; Bhalla, Sean; Amin, Sunil; Kumar, Shria
ABSTRACT: Neurofibromas are peripheral nerve sheath tumors that are typically seen in syndromic conditions such as neurofibromatosis 1. We present the case of a 26-year-old woman suffering from chronic abdominal pain for over 5 years. Prior workup showed a large retroperitoneal mass extending into the abdomen and encasing multiple major vessels. She underwent endoscopic ultrasound (EUS)-guided biopsy, which was histologically consistent with a solitary neurofibroma. There is no prior report of solitary neurofibroma of the abdomen diagnosed with the use of EUS-guided biopsy. This case highlights the utility of EUS-guided biopsy in the evaluation of intra-abdominal pathology.